2017
DOI: 10.3233/jin-170061
|View full text |Cite
|
Sign up to set email alerts
|

Did you know that your animals have consciousness?

Abstract: Consciousness is the greatest enigma in human history. For centuries scientists and researchers have tried to describe it without coming to conclusions. In the last years with the neurosciences development, consciousness has become the common goal of numerous studies. But consciousness has always been studied only in humans, but after "Cambridge Declaration on Consciousness" in 2012, even non-human animalsthey feel possessed of the consciousness. According to "theory Orch-OR" of Hameroff and Penrose we have co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…For example, administration of citicoline or CDPcholine, which are PC precursors, significantly improves electroencephalographic tracing and alleviates consciousness impairment after head injury [51,52]. Similar to PC, AA also participates in the molecular and cellular pathways of consciousness [53].…”
Section: Discussionmentioning
confidence: 99%
“…For example, administration of citicoline or CDPcholine, which are PC precursors, significantly improves electroencephalographic tracing and alleviates consciousness impairment after head injury [51,52]. Similar to PC, AA also participates in the molecular and cellular pathways of consciousness [53].…”
Section: Discussionmentioning
confidence: 99%
“…I could never know what she was thinking, and why she was acting in the way she did, but our close relationship made it possible for me to understand her through my own body. Such empathetic connections are possible across species since humans and other species have molecular analogies for moods and emotions (Accorsi et al, 2017).…”
Section: Multispecies Ethnographymentioning
confidence: 99%
“…In recent years, several studies have shown that depression is not just a human disease but it has a molecular affinity within the animal kingdom [1,2]. Until now, research on depression have mainly been focused on the genetic, behavioral and neurological aspects of the mental illness.…”
Section: Introductionmentioning
confidence: 99%
“…Based on this similarity, they were able to identify different mood disorders (Major Depression and Bipolar Disorder) by creating an artificial neural network, whose crucial factors were three fatty acids (i.e., Palmitic Acid, Linoleic Acid, Arachidonic Acid) [10,11]. The same study was conducted taking into account different animal species and its most important evidence was the molecular similarity between two particular dog breeds (German Shepherd and Alaskan Malamute) and humans affected by Major Depression and Bipolar Disorder [2,12,13]. Considering the molecular similarity in fatty acids platelets between German Shepherds and humans suffering from depression and the studies on the gut-microbiota of the latter, the aim of this research was to analyze the gut-microbiota composition of German Shepherd in comparison to other canine mixed breeds not described as the suffering of depression disease.…”
Section: Introductionmentioning
confidence: 99%